Mythmaking in motivation of the medical institution staff - Hromtsev, Kostiantyn; Krupskyi, Oleksandr; Stasiuk, Yuliia (Management and Entrepreneurship: Trends of Development, 2025)
In the modern context of healthcare system transformation, high levels of professional burnout among medical workers, and the increasing need to enhance human resource management efficiency, intangible methods of motivation are becoming particularly important. One such tool is organizational mythmaking – the deliberate creation of corporate myths, symbols, rituals, and positive narratives that foster emotional engagement, increase job satisfaction, strengthen team cohesion, and enhance employees’ identification with the medical institution. The purpose of this study is to substantiate the effectiveness of organizational mythmaking as a tool of non-material motivation for personnel in medical institutions and to identify the mechanisms of its implementation in management practices. The object of the study involves social processes and communication strategies that support the symbolic reinforcement of corporate culture in healthcare institutions. Methodologically, the article relies on an interdisciplinary approach that includes elements of organizational behavior, the sociology of myth, medical communication, and human resource management. The methods used include content analysis of heroized images of doctors in public discourse, qualitative analysis of symbolic elements (logos, rituals, narratives), and case study analysis illustrating the formation of a positive image and professional inspiration. The findings confirm that conscious development of corporate myths centered around the mission of the institution, heroic images of physicians, collective achievements, and professional dedication contribute to increased internal motivation, reduced emotional burnout, and improved communication within teams. The authors highlight key areas of mythmaking implementation: success stories, symbolic attributes, regular recognition rituals, and the formation of a positive social capital around the institution. The article also draws attention to potential risks of mythmaking, particularly the danger of creating artificial, inauthentic myths that may lead to distrust or skepticism among employees. To mitigate this, the authors propose principles of “ethical mythmaking” based on real achievements, transparency, collective recognition, and adherence to professional ethics. Thus, the conclusions of the study suggest that organizational mythmaking is a promising tool of strategic human resource management in healthcare. Its application supports not only the effectiveness of motivational policies but also the formation of a sustainable, emotionally cohesive, and value-oriented professional community capable of responding to modern challenges. JEL Classification: I12, M12, Z13